Hydrogen Sulfide, Oxidative Stress and Periodontal Diseases: A Concise Review - Maria Greabu; Alexandra Totan; Daniela Miricescu; Radu Radulescu; Justina Virlan; Bogdan Calenic (MDPI AG, 2016)
In the past years, biomedical research has recognized hydrogen sulfide (H2S) not only as an environmental pollutant but also, along with nitric oxide and carbon monoxide, as an important biological gastransmitter with paramount roles in health and disease. Current research focuses on several aspects of H2S biology such as the biochemical pathways that generate the compound and its functions in human pathology or drug synthesis that block or stimulate its biosynthesis. The present work addresses the knowledge we have to date on H2S production and its biological roles in the general human environment with a special focus on the oral cavity and its involvement in the initiation and development of periodontal diseases.